SEEDLING GROWTH OF MAIZE INBRED LINES (Zea mays L.) AS A RESPONSE TO SEED TREATMENT WITH PESTICIDES - Tamindžić, Gordana; Nikolić, Zorica; Savić, Jasna; Milošević, Dragana; Petrović, Gordana; Ivanović, Dragana; Ignjatov, Maja (Journal of Agricultural Sciences (Belgrade), 2016)
Abstract: Seed treatment is a common way of fungicide and insecticide use nowadays, since this way of pesticide application can provide the best protection in the vicinity of the future plant. The aim of research was to evaluate the effects of different seed treatments on germination and seedling growth in three maize inbred lines. The research included seed treatment with several combinations of a fungicide Maxim XL 035-FS and neonicotinoid insecticides Gaucho 600-FS and Cruiser 350-FS, as well as untreated seed (control). The results indicated that inbred lines 21202 x 21101 NS and 317659 NS had highly vigourous seed, which were not affected by the seed treatments. Seed treatments with Maxim XL 035-FS+Gaucho 600-FS and Maxim XL 035-FS+Cruiser 350-FS led to a decrease in germination of maize inbred line 306081 NS as well as a decrease in root length and dry root weight of maize inbred line 21202 x 21101 NS. All seed treatments had positive effects on root growth, as well as on fresh root weight of maize inbred lines 306081 NS and 317659 NS.